A case of tongue swelling after intravenous recombinant tissue plasminogen activator administration for acute ischemic stroke - Murat Cabalar (Türk Beyin Damar Hastalıkları Dergisi, 2017)
A 70-year-old man was admitted to our hospital with acute stroke. He had a history of hypertension with trandolapril-verapamil 4/240 mg per day therapy. He had confusion and right-sided hemiplegia. Diffusion magnetic resonance imaging revealed an ischemic lesion on the left middle cerebral artery territory. After receiving intravenous (iv) recombinant tissue plasminogen activator (r-tPA) infusion, he developed tongue swelling. With standard anti anaphylactic medication tongue swelling disappeared. Termination of iv r-tPA may not be required in some tongue swelling cases. Timing of angioedema, circumstances under which iv r-tPA is administered and the severity of relevant respiratory problems may be helpful in the decision of termination or continuation of iv r-tPA administration.